APLIKASI RAIN GARDEN DUA FASE UNTUK PERBAIKAN KUALITAS AIR LIMBAH INDUSTRI SASIRANGAN - Lopes, Winfrida Nonie (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2024)
Atun Cempaka Production House is one of the sasirangan craftsmen where the liquid waste produced when producing sasirangan cloth is not processed and is directly disposed of into water bodies. Sasirangan liquid waste that is directly discharged into water bodies has many negative impacts on the environment. Based on laboratory tests on liquid waste produced by the Atun Cempaka Production House, it was found that the concentration of COD was 1956.62 mg/L and TSS was 339 mg/L, which were not in accordance with the quality standards according to Permen LHK No. P. 16 of 2019, 150 mg/L for COD and 50 mg/L for TSS. Rain garden is a rainwater bioretention area which can filter pollutants and heavy metal content in rainwater. Rain garden with a two-phase system is an alternative that has just been developed. Efforts to improve the quality of sasirangan industrial wastewater are carried out by combining the rain garden systems in stages. The research was conducted on a laboratory scale using 3 variations of planting media, namely Sand Compost, Compost Pallet I, and Compost Pallet II, and using contact times of 0 minutes, 30 minutes and 60 minutes. The results showed that the efficiency of reducing COD and TSS concentrations using a variety of growing media Sand Compost was higher than Compost Pallet I and Compost Pallet II. The reduction efficiency of COD and TSS using the Sand Compost planting media variation was 93.88% and 88.33%, while the COD and TSS reduction efficiency for the Compost Pallet I planting media variation was 93.48% and 79.25% and for the Compost Pallet II was 93.59% and 85,71%.